2009
DOI: 10.1111/j.1742-1241.2009.02129.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential savings without compromising the quality of care

Abstract: A substantial amount of money can be saved in primary care without compromising the quality of care by using recommended first-line drugs for the treatment diabetes, hypertension and hypercholesterolaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…generic simvastatin [5-8, 11, 14, 15, 17, 19, 25]. These beliefs are endorsed by a recent ecological study, which showed that outcomes, in terms of the subsequent impact of drug treatment on lipid levels, were similar whether patients were prescribed formulary drugs (including generic simvastatin) versus non-formulary drugs, which included patent-protected statins [32]. Published studies have also shown that patients can be successfully switched from atorvastatin to simvastatin without compromising care [33], and physicians in UK extensively prescribe generic simvastatin to achieve agreed target lipid levels in the quality and outcomes framework to help maximise their income [14,21,34,35].…”
Section: Review Articlementioning
confidence: 53%
See 1 more Smart Citation
“…generic simvastatin [5-8, 11, 14, 15, 17, 19, 25]. These beliefs are endorsed by a recent ecological study, which showed that outcomes, in terms of the subsequent impact of drug treatment on lipid levels, were similar whether patients were prescribed formulary drugs (including generic simvastatin) versus non-formulary drugs, which included patent-protected statins [32]. Published studies have also shown that patients can be successfully switched from atorvastatin to simvastatin without compromising care [33], and physicians in UK extensively prescribe generic simvastatin to achieve agreed target lipid levels in the quality and outcomes framework to help maximise their income [14,21,34,35].…”
Section: Review Articlementioning
confidence: 53%
“…Alongside this, pharmaceutical companies have failed to provide reimbursement agencies with any published studies documenting increased effectiveness of ARBs versus ACEIs to support premium prices for ARBs [26,27]. In addition, only 2-3% of patients in the ACEI clinical trials actually discontinued ACEIs due to coughing [36,37], and a recent ecological study again showed that outcomes, in terms of the subsequent impact of drug treatment on blood pressure, were similar whether patients were prescribed formulary drugs (including generic ACEIs) versus non-formulary drugs, which included patent-protected ARBs [32]. As a result, generic ACEIs can be prescribed first line with patent-protected ARBs reserved for patients where there are concerns with side effects without compromising outcomes.…”
Section: Review Articlementioning
confidence: 99%
“…High adherence rates at 80 to 90%% to the voluntary Wise List are enhanced by the involvement of prescribers in the selection process, a comprehensive communication program including a separate list for both patients and physicians, physician trust in the guidance, as well as regular feedback (24,65). Increased adherence also reduces costs (21,24,66). There are similar examples in Spain and Scotland (12,60,65).…”
Section: Discussionmentioning
confidence: 88%
“…Accumulated savings could increase to 49 million CNY with the attainment of generic prices similar to low prices achieved in some Western European countries. Simvastatin is recommended in the 'Wise List' in Stockholm County Council (66). In addition, SIGN (Scottish Intercollegiate Guidelines Network) in Scotland advocate the use of only 40 mg simvastatin for the prevention of cardiovascular disease (68,69) as well as for primary prevention of cardiovascular disease in patients with Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially reduce adverse drug reactions and drug: drug [52][53][54][55]. Research findings have also shown that increased adherence to the Wise List also reduces costs since medicines that have the most robust data tend to be well established medicines [52,55,56]. There are similar examples in Spain and Scotland [9,10,53].…”
mentioning
confidence: 78%